Migration law of flax threshing materials in double channel air-and-screen separating cleaner - Dai, Fei; Song, Xuefeng; Shi, Ruijie; Zhao, Wuyun; Guo, Wenjuan; Zhang, Yang (International Journal of Agricultural and Biological Engineering, 2021)
In order to further clarify and improve the working performance of separating cleaner for flax threshing materials, and study the migration law and characteristics of components of flax threshing materials during separating and cleaning, in this paper, a gas-solid coupling simulation model was established on the separation cleaner for flax threshing materials and a numerical simulation was carried out on the separating and cleaning process. Simulation results showed that, the separating and cleaning effect of the components of flax threshing materials was good under the air-and-screen gas-solid coupling flow field. Meanwhile, the form distribution and the vector distribution of air volume and velocity of flax threshing materials in the air-and-screen devices were obtained. By referring to the migration trajectories of the flax threshing materials in the vibration sieve device, double channel residue collection device and dust absorber, the volume variation, motion trajectories and variation of migration velocity of the components of flax threshing materials over time in different regions were explored. Verification test results showed that, the content impurity rate of the separation cleaner for flax threshing materials was 2.06%, and loss rate in cleaning was 3.08%. Compared with simulation results, the verification test results were 1.23% and 0.42% higher, showing that the established discrete element model on the flax threshing materials and parameter setting were basically feasible. The verification test also verified the correctness of the simulation results of the separating and cleaning process of the flax threshing materials based on gas-solid coupling theory and the feasibility of the research method.Keywords: flax threshing materials, separation cleaner, air-and-screen, gas-solid coupling, discrete element model, numerical simulationDOI: 10.25165/j.ijabe.20211403.6058Citation: Dai F, Song X F, Shi R J, Zhao W Y, Guo W J, Zhang Y. Migration law of flax threshing materials in double channel air-and-screen separating cleaner. Int J Agric & Biol Eng, 2021; 14(3): 92–102.